Leishmania (Viannia) panamensis expresses a nuclease with molecular andbiochemical features similar to the Endonuclease G of higher eukaryotes (2011)
ABSTRACT: Objective: To characterize the molecular and biochemical features of the Endonuclease G of Leishmania (Viannia) panamensis. Methods:The gene of the putative L. (V.) panamensis Endonuclease G was amplified, cloned, and sequenced. The recombinant protein was produced in a heterologous expression system and biochemical assays were run to determine its ion,temperature, and pH preferences. Results: The L. (V.) panamensis rENDOG has biochemical features similar to those found in other trypanosomatids and higher eukaryotes. In addition, phylogenetic analysis revealed a possible evolutionary relationship with metazoan ENDOG. Conclusions: L. (V.) panamensis has a gene that codifies an ENDOG homologous to those of higher organisms. This enzyme can be produced in Escherichia coli and is able to degrade covalently closed circular double-stranded DNA. It has a magnesium preference, can be inhibited by potassium, and is able to function within a wide temperature and pH range.